2005
DOI: 10.1677/joe.1.06110
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pancreatic acinar cell proliferation by thyroid hormone

Abstract: Thyroid hormone is known to elicit diverse cellular and metabolic effects in various organs, including mitogenesis in the rat liver. In the present study, experiments were carried out to determine whether thyroid hormone is able to stimulate cell proliferation in another quiescent organ such as the pancreas. 3,5,3 --tri-iodothyronine (T3) added to the diet at a concentration of 4 mg/kg caused a striking increase in nuclear bromodeoxyuridine (BrdU) incorporation of rat acinar cells 7 days after treatment (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…However, it has been clearly demonstrated that in several organs of the gastrointestinal tract, THs-TRs stimulate cell proliferation. This effect has been documented in rat liver and pancreas (Ledda- Columbano et al, 2005;Columbano et al, 2006), as well as in renal proximal tubular epithelial cells (Ohmura et al, 1997). Indeed, THs activate proliferation of hepatocytes after partial hepatectomy and are, in fact, considered primary liver mitogens (Francavilla et al, 1994;Malik et al, 2003;Alisi et al, 2005;Bockhorn et al, 2007).…”
Section: -Tissue-specific Action Of Ths and Trs In The Intestinementioning
confidence: 78%
“…However, it has been clearly demonstrated that in several organs of the gastrointestinal tract, THs-TRs stimulate cell proliferation. This effect has been documented in rat liver and pancreas (Ledda- Columbano et al, 2005;Columbano et al, 2006), as well as in renal proximal tubular epithelial cells (Ohmura et al, 1997). Indeed, THs activate proliferation of hepatocytes after partial hepatectomy and are, in fact, considered primary liver mitogens (Francavilla et al, 1994;Malik et al, 2003;Alisi et al, 2005;Bockhorn et al, 2007).…”
Section: -Tissue-specific Action Of Ths and Trs In The Intestinementioning
confidence: 78%
“…Endogenous TR is insufficient for induction of expression of the cyclin D1 protein that activates the cyclin D1/CDK/Rb pathway. Previous reports have indicated that thyroid hormone enhances pancreatic acinar cell proliferation (35) and ␤-cell proliferation (36) in vitro. These results were compatible with our in vivo findings that overexpression of TR␣1 enhances ␤-cell proliferation in STZ-treated mice.…”
Section: Discussionmentioning
confidence: 96%
“…Plate chondrocyte hypertrophic differentiation (23), cardiomyocyte growth (24), neuronal and glial cell differentiation (25), and primary B lymphopoiesis (26) are influenced by TH. T 3 is also a powerful inducer of pancreatic acinar cell proliferation in rodents (27). b-Cell mass is determined by a balance between b-cell replication, size, and neogenesis, and rate of b-cell apoptosis (28).…”
Section: Discussionmentioning
confidence: 99%